The Attitudes of Teachers on the Use of First Language in English - Hamza Zeebaree (Journal of Research in Social Sciences and Language)
This study examines the use of the first language (L1), here Kurdish or Arabic, from the perspective of teachers in the process of teaching and learning English in EFL classrooms at the English Department, College of Languages, the University of Duhok in Kurdistan. The study investigates four different areas; the first one is to find out if the English Department/ the College of Languages have a policy for the teachers for using L1. The second one is to investigate if the use of L1 is a necessity. The study also investigates whether the use of L1 facilitates or hinders the teaching and learning of English at the department/college. Finally, it explores if the teachers’ use of L1 is based on other bases rather than the policy set by the department or the college if there is any policy. The last part presents the results of the study; the study concludes that there are no specific policies administrated neither by the English Department nor the College of the languages to use L1. In addition, judicious and limited use of L1 by teachers is a better approach to take in EFL classes than to include or exclude it totally, and the use of L1 is mostly based on the students’ needs and lesson content.